Can might make rights?: Building the rule of law after military interventions - Stromseth, Jane E (Cambridge University, 2013)
This book looks at why it is so difficult to create "the rule of law" in post-conflict societies such as Iraq and Afghanistan and offers critical insights into how policymakers and field-workers can improve future rule of law efforts. Aimed at policymakers, field-workers, journalists, and students trying to make sense of the international community's problems in Iraq and elsewhere, this book shows how a narrow focus on building institutions such as courts and legislatures misses the more complex political and cultural issues that affect societal commitment to the values associated with the rule of law. The authors place the rule of law in context, showing the interconnectedness between the rule of law and other post-conflict priorities, from reestablishing security to revitalizing civil society. The authors outline a pragmatic, synergistic approach to the rule of law that promises to reinvigorate debates about transitions to democracy and post-conflict reconstruction.